The prospective effects of long-term exposure to ambient PM2.5 and constituents on mortality in rural East China. (October 2021) - Chen, Yun; Chen, Renjie; Chen, Yue; Dong, Xiaolian; Zhu, Jianfu; Liu, Cong; van Donkelaar, Aaron; Martin, Randall V.; Li, Huichu; Kan, Haidong; Jiang, Qingwu; Fu, Chaowei
Abstract: Few cohort studies explored the associations of long-term exposure to ambient fine particulate matter with an aerodynamic diameter of 2.5 μm or less (PM2.5 ) and its chemical constituents with mortality risk in rural China. We conducted a 12-year prospective study of 28, 793 adults in rural Deqing, China from 2006 to 2018. Annual mean PM2.5 and its constituents, including black carbon (BC), organic carbon (OC), ammonium (NH4 + ), nitrate (NO3 − ), sulfate (SO4 2− ), and soil dust were measured at participants' addresses at enrollment from a satellite-based exposure predicting model. Cox proportional hazard model was used to estimate hazard ratios (HRs) and 95% confidence intervals (95%CIs) of long-term exposure to PM2.5 for mortality. A total of 1960 deaths were identified during the follow-up. We found PM2.5, BC, OC, NH4 +, NO3 −, and SO4 2− were significantly associated with an increased risk of non-accidental mortality. The HR for non-accidental mortality was 1.17 (95%CI: 1.07, 1.28) for each 10 μg/m 3 increase in PM2.5 . As for constituents, the strongest association was found for BC (HR = 1.21, 95%CI: 1.11, 1.33), followed by NO3 −, NH4 +, SO4 2−, and OC (HR = 1.14–1.17 per interquartile range). A non-linear relationship was found between PM2.5 and non-accidental mortality. Similar associations were found for cardio-cerebrovascular and cancer mortality. Associations were stronger among men and ever smokers. Conclusively, we found long-term exposure to ambient PM2.5 and its chemical constituents (especially BC and NO3 − ) increased mortality risk. Our results suggested the importance of adopting effective targeted emission control to improve air quality for health protection in rural East China. Highlights: First cohort on PM2.5 and constituents with mortality in rural Eastern China. Long-term exposure to PM2.5 increases risk of non-accidental mortality. Black carbon has the strongest association compared to other PM2.5 constituents. There is a non-linear relationship between PM2.5 and non-accidental mortality. Sex, smoking status are effect modifiers of air pollution and mortality.